Effect of autotransplantation of a parathyroid gland on hypoparathyroidism after total thyroidectomy. Issue 2 (February 2018) - Su, Anping; Gong, Yanping; Wu, Wenshuang; Gong, Rixiang; Li, Zhihui; Zhu, Jingqiang
Abstract : Background: The effect of parathyroid autotransplantation on hypoparathyroidism is not fully understood. The purpose of the study was to determine the effect of autotransplantation of a parathyroid gland on the incidence of hypoparathyroidism and recovery of parathyroid function at 6 months after total thyroidectomy with central neck dissection for papillary thyroid carcinoma. Methods: All patients with autotransplantation of a parathyroid gland (no inadvertent parathyroidectomy) (group A), in situ preservation of all parathyroid glands (no autotransplantation and inadvertent parathyroidectomy) (group B) or inadvertent removal of a parathyroid gland (no autotransplantation) (group C) who underwent first-time total thyroidectomy with central neck dissection for papillary thyroid carcinoma between January 2013 and June 2016 were included retrospectively. Results: Of the 702 patients, 383, 297 and 22 were respectively included in the groups A, B and C. The overall rates of transient and permanent hypoparathyroidism were 37.6% and 1.0%. The incidence of transient hypoparathyroidism was 43.9, 29.0 and 45.5% (A vs B, P  = 0.000; A vs C, P  = 1.000), and the incidence of permanent hypoparathyroidism was 1.0, 0.7 and 4.5% ( P  > 0.05). The recovery rates of serum parathyroid hormone levels were 71.4, 72.2 and 66.0% at 6-month follow-up ( P  > 0.05). Conclusion: Autotransplantation of a parathyroid gland does not affect the incidence of permanent hypoparathyroidism, but increases the risk of transient hypoparathyroidism when the rest of parathyroid glands are preserved in situ . At least 2 parathyroid glands should be preserved during total thyroidectomy with central neck dissection to prevent permanent hypoparathyroidism.